Association of Compartmental Bone Bruise Distribution With Concomitant Intra-articular and Extra-articular Injuries in Acute Anterior Cruciate Ligament Tears After Noncontact Sports Trauma - Aravindh, P. (SAGE Publications Ltd, 2021)
10.1177/2325967118767625